Integrating ethnoscience in inquiry-creative learning: a new breakthrough in enhancing critical thinking - Harjono, Ahmad; Verawati, Ni Nyoman Sri Putu; Wahyudi, Wahyudi; Gummah, Syifa'ul; Prayogi, Saiful (Institute of Advanced Engineering and Science, 2025)
Incorporating knowledge of culture and local wisdom values (ethnosciences) into scientific investigation is a new breakthrough in the current study. The integration of ethnosciences and scientific investigation is a valuable pathway that serves not only as a tool for acquiring new knowledge but also for developing critical thinking (CT) skills essential in solving real-world problems. This research aims to enhance CT skills among prospective science teachers (PSTs) through a teaching program that integrates ethnosciences with inquiry-creative learning. This particular investigation employs a mixed method approach, combining both quantitative and qualitative methods. The quantitative study utilized a randomized pretest-posttest control group design, with traditional expository teaching employed as the comparison group. Qualitative methods were specifically used in this study through semi-structured interviews with lecturer, particularly regarding the PSTs’ engagement in the implementation of learning program. CT skill tests and interview forms were used as data collection instruments. The study findings reveal that integrating ethnosciences with inquiry-creative learning has a significant effect on the development of CT skills compared to traditional instruction. The findings highlight the effectiveness of this approach in improving CT skills among PSTs and contribute to future research in the field of science education.